Development of lung segmentation method in x-ray images of children based on TransResUNet - Chen, Lingdong; Yu, Zhuo; Huang, Jian; Shu, Liqi; Kuosmanen, Pekka; Shen, Chen; Ma, Xiaohui; Li, Jing; Sun, Chensheng; Li, Zheming; Shu, Ting; Yu, Gang (Frontiers in Radiology, 2023)
Background Chest x-ray (CXR) is widely applied for the detection and diagnosis of children's lung diseases. Lung field segmentation in digital CXR images is a key section of many computer-aided diagnosis systems. Objective In this study, we propose a method based on deep learning to improve the lung segmentation quality and accuracy of children's multi-center CXR images. Methods The novelty of the proposed method is the combination of merits of TransUNet and ResUNet. The former can provide a self-attention module improving the feature learning ability of the model, while the latter can avoid the problem of network degradation. Results Applied on the test set containing multi-center data, our model achieved a Dice score of 0.9822. Conclusions This novel lung segmentation method proposed in this work based on TransResUNet is better than other existing medical image segmentation networks.